2010
DOI: 10.1080/02678371003703859
|View full text |Cite
|
Sign up to set email alerts
|

Are workers in high-status jobs healthier than others? Assessing Jahoda's latent benefits of employment in two working populations

Abstract: It is known that employment is important for psychological health. The present paper claims that the reasons why employed persons report better well-being than unemployed persons might also explain why those in some occupations report better well-being than others. Jahoda's latent deprivation theory (1982) was that employment provides a number of latent beneficial functions, which she identified as time structure, social contact, collective purpose, identity/status, and activity. We argue that this theory can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 25 publications
1
54
0
1
Order By: Relevance
“…The finding that managers are generally less stressed than nonmanagers was also consistent with previous reported findings (e.g., Batinic et al, 2010). Several studies have shown that high level employment is positively related with good health (Andersen, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…The finding that managers are generally less stressed than nonmanagers was also consistent with previous reported findings (e.g., Batinic et al, 2010). Several studies have shown that high level employment is positively related with good health (Andersen, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…Uncertainty elicits feelings of powerlessness and lack of control, and such perceptions of uncontrollability, in turn, have been shown to be important antecedents of impaired health (Bordia et al, 2004). The negative consequences of job insecurity can additionally be explained on the basis of Jahoda's latent deprivation model (Batinic, Selenko, Stiglbauer, & Paul, 2010;Jahoda, 1982). In her model, Jahoda (1982) documents the needs which can be satisfied by employment, such as earning an income, having social contacts outside the family, being able to structure one's time and to develop individually and socially.…”
Section: Job Insecurity and Employee Healthmentioning
confidence: 97%
“…The literature is divided as to whether to treat the latent benefits as partial constructs or as one overall construct. Both conceptions have gained empirical support, but recent studies indicate that not only persons in different employment statuses vary regarding their access to different latent benefits but also that the latent benefits vary in their impact on psychological health (Batinic, Selenko, Stiglbauer, & Paul, 2010; Hassall et al , 2004; Hoare & Machin, in press; Paul & Batinic, 2010; Waters & Moore, 2002a).…”
Section: Introductionmentioning
confidence: 99%